Effect of feeding Bacillus cereus var. toyoi and/or mannan oligosaccharide (MOS) on blood clinical chemistry, oxidative stress, immune response and genotoxicity in T-2 toxin exposed rabbits. Issue 1 (2nd January 2019) - Hafner, Dóra; Tuboly, Tamás; Mézes, Miklós; Bloch-Bodnár, Zsófia; Balogh, Krisztián; Vántus, Viola; Bóta, Brigitta; Szabó-Fodor, Judit; Matics, Zsolt; Szabó, András; Kovács, Melinda
Abstract: The aim of the study was to determine the effect of Bacillus cereus var. toyoi (200 mg/kg) and mannan oligosaccharide (MOS, 2 g/kg) in T-2 toxin exposed rabbits. Weaned rabbits (35 days of age) were assigned into four experimental groups ( n = 20 in each): control (C), B. cereus (B), MOS (M) and B. cereus +MOS (BM) group. At 49 days of age, rabbits were divided into two groups ( n = 10 in each), and half of the C, B, M and BM rabbits were fed with the same diet as before, but contaminated with 2 mg/kg feed T-2 toxin (groups CT, BT, MT and BMT). On day 50 and 60, rabbits were injected with ovalbumin. At 70 days of age, all animals were sacrificed. Daily weight gain was smaller in toxin challenged animals (17.6–19.5 g) compared to controls (29.7 g). Serum total protein concentration was less in toxin treated animals, among them in CT group (49.7 g/L) it decreased underneath the reference range. T-2 increased the glutathione peroxidase activity in the kidney. C and B treatments resulted in the highest IgG production. Phagocytic activity was the lowest in CT animals (76.4%), while the highest in C and BM groups (82%). Cytokine expression in the intestinal mucosa was lower in T-2 exposed animals as compared to their relevant controls. None of the feed additives had any effect on the T-2 induced changes in the oxidative stress and immune response. T-2 had slight genotoxic effect on lymphocytes, which was alleviated by MOS and B. cereus . Highlights: The suspected protective effect of Bacillus cereus var. toyoi and mannan oligosaccharide was investigated in T-2 toxin exposed rabbits. T-2 impaired immune response and was slightly genotoxic on lymphocytes. MOS and B. cereus alleviated the genotoxicity of T-2.